Do profitability ratio and market ratio contribute to explain the movement of stock prices of transport companies? - Sitty Shandragies Usman; Idham Masri Ishak; Selvi Selvi (Universitas Negeri Gorontalo, 2020)
This study aims to determine the effect of profitability ratios and market ratios on stock prices on transportation companies listed on the Indonesia Stock Exchange with the study period of 2013-2017. Profitability ratios used in this study are Return On Assets (ROA) and Return On Investment (ROI) and Market Ratios used in this study are Price Earning Ratio (PER) and Market to Book Value (MBV) to stock prices. The sample in this study were 24 transportation companies listed on the IDX. The data analysis method in this research is multiple linear regression which aims to obtain a comprehensive picture of the effect of the Profitability Ratio and Market Ratio variables on stock prices using the SPSS program. The results showed that only partially market ratio variables had an effect on stock prices both measured by PER and MBV while profitability ratio variables measured by ROA and ROI simultaneously had no effect on stock prices. Simultaneously shows that all variables namely profitability ratios and market ratios together have an influence on the stock prices of transport companies listed on the Indonesia Stock Exchange in 2013-2017.